Training And Research Studies Of Future Bachelor’s Mathematicians During The Study Limits - Balausa Kalmatayeva, Burkhan Kalimbetov, Indira Omarova,; Ibragimov, Raskul (Opción, 2019)
The paper deals with issues of improving the effectiveness of professional training of bachelors in mathematics due to the intensification of their research activities by applying asymptotic expansions. In result, the non-effectiveness of applying the standard asymptotic expansions to them can be explained by the fact that their direct application does not allow to allocate in the numerators of the given fractions the main part which is not identically equal to zero. In conclusion, research activities are the resulting intellectual product that sets a certain truth in a particular subject area, new knowledge based on existing knowledge and skills.